Perspektif Hukum dan Pertanggungjawaban Pidana terhadap Tindak Pidana Sektor Perbankan - Firmantoro, Kiki; Adilang, Agam Alusinsing; Nugroho, Meysita Arrum (PT Elaborium Elevasi Indonesia, 2024)
Current economic life is closely related to the banking sector, which plays a role in meeting human needs through bank operations. Law Number 10 of 1998 concerning Amendments to Law Number 7 of 1992 concerning Banking, known as the Banking Law, strictly defines a bank as a business entity that collects funds from the public in the form of savings and allocates them to the public in the form of credit and various forms, all of which aim to improve the standard of living of many people. This research adopts a qualitative approach using normative legal methods as the main framework. The data collected is descriptive in nature and obtained from various sources, including documents, interviews, and observations of individuals involved in this study. Banks are a form of corporate entity that has equal legal status to individuals, regardless of organizational structure. They also have the ability to act according to the law, file lawsuits, and litigate in court. In the context of banking crime, there are several dimensions that need to be considered. This includes individual criminal acts against banks, bank criminal acts against other banks, or bank crimes against individuals. Banks can be victims or perpetrators in this context. In addition, banking crimes are not limited to the territorial borders of a country and can occur in the short or long term. The scope of banking crime covers all aspects of banking life and related financial institutions and includes written and unwritten banking norms, all with regulated criminal sanctions.